Managing in recovering markets - Chatterjee, S.; Singh, N.P; Goyal, D.P; Gupta, Narain (Springer Proceedings in Business and Economics,, 2015)
The changing dynamics of business worldwide have led organizations to look beyond traditional managerial practices while at the same time attempting to retain their core competitive advantages. This development has called upon academicians and practitioners alike to reassess the different aspects of business management such as macroeconomic variables, the nature of the market, the changing features of the workplace, the new work ethos, and/or employer-employee exchanges. In this context, the book provides essential insights on industry innovations, academic advances, and policy movements with regard to recovering markets in India and around the globe. The individual papers highlight potential avenues that could allow industry to better understand and respond to the global crisis. The book collects research papers presented at the Global Conference on Managing in Recovering Markets (GCMRM), held in March 2014. Seven international and 120 national business schools and management universities were represented at the conference, the first in a series of 13 planned under the GCMRM agenda for 2014-17. The book includes more than 30 research papers chosen from a pool of 118 presented at the conference, all of which have undergone a rigorous blind review process.